Endocarditis and monocular blindness. (26th October 2016) - Andrews, Jack; Borooah, Shyamanga
Abstract : A man aged 77 years with postrenal transplant lymphoproliferative disease was admitted with high fever, elevated inflammatory markers and a heart murmur. Blood cultures grew Enterococcus faecalis and he was found to have mitral valve endocarditis on echocardiogram and subsequently started on appropriate antibiotics. 5 days into treatment, he developed ocular symptoms and 3 days later, he had irreversible monocular visual loss. He was seen by the ophthalmology team who diagnosed endogenous endopthalmitis secondary to bacteraemic spread from his endocarditis. Despite treatment with intravitreal antibiotics and prolonged systemic antibiotics, his sight did not recover. Although septic emboli are common in endocarditis, endogenous endophthalmitis is rarely reported and frequently results in visual loss. Early treatment confers an improved prognosis.